Atomic force microscopy study of the antigen‐antibody binding force on patient cancer cells based on ROR1 fluorescence recognition. Issue 9 (8th July 2013) - Li, Mi; Xiao, Xiubin; Liu, Lianqing; Xi, Ning; Wang, Yuechao; Dong, Zaili; Zhang, Weijing
<x xml:space="preserve">Abstract</x> Knowledge of drug–target interaction is critical to our understanding of drug action and can help design better drugs. Due to the lack of adequate single‐molecule techniques, the information of individual interactions between ligand‐receptors is scarce until the advent of atomic force microscopy (AFM) that can be used to directly measure the individual ligand‐receptor forces under near‐physiological conditions by linking ligands onto the surface of the AFM tip and then obtaining force curves on cells. Most of the current AFM single‐molecule force spectroscopy experiments were performed on cells grown in vitro (cell lines) that are quite different from the human cells in vivo. From the view of clinical practice, investigating the drug–target interactions directly on the patient cancer cells will bring more valuable knowledge that may potentially serve as an important parameter in personalized treatment. Here, we demonstrate the capability of AFM to measure the binding force between target (CD20) and drug (rituximab, an anti‐CD20 monoclonal antibody targeted drug) directly on lymphoma patient cancer cells under the assistance of ROR1 fluorescence recognition. ROR1 is a receptor expressed on some B‐cell lymphomas but not on normal cells. First, B‐cell lymphoma Raji cells (a cell line) were used for ROR1 fluorescence labeling and subsequent measurement of CD20‐rituximab binding force. The results showed that Raji cells expressed ROR1, and the labeling of ROR1 did not influence the measurement of CD20‐rituximab binding force. Then the established experimental procedures were performed on the pathological samples prepared from the bone marrow of a follicular lymphoma patient. Cancer cells were recognized by ROR1 fluorescence. Under the guidance of fluorescence, with the use of a rituximab‐conjugated tip, the cellular topography was visualized by using AFM imaging and the CD20‐Rituximab binding force was measured by single‐molecule force spectroscopy. Copyright © 2013 John Wiley & Sons, Ltd.